2021
DOI: 10.1038/s41419-021-04186-6
|View full text |Cite
|
Sign up to set email alerts
|

BRD9 inhibition promotes PUMA-dependent apoptosis and augments the effect of imatinib in gastrointestinal stromal tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are primarily characterized by activating mutations of tyrosine kinase or platelet-derived growth factor receptor alpha. Although the revolutionary therapeutic outcomes of imatinib are well known, the long-term benefits of imatinib are still unclear. The effects of BRD9, a recently identified subunit of noncanonical BAF complex (ncBAF) chromatin remodeling complexes, in GISTs are not clear. In the current study, we evaluated the functional role of BRD9 in GIST progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The interaction of BRD9 with SWI/SNF complexes represents an area of much current interest for cancer treatment [ 30 , 31 , 32 ]. BRD9 is overexpressed in many malignancies, including CRC ( Figure 1 ) and Gastrointestinal Stromal Tumors (GISTs) [ 33 ]. We observed that siRNA-mediated loss of BRD9 expression in human colon cancer cells produced marked changes in phenotypic and molecular readouts ( Figure 2 ), consistent with the overarching goal of targeting oncogenic functions arising from BRD9 overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of BRD9 with SWI/SNF complexes represents an area of much current interest for cancer treatment [ 30 , 31 , 32 ]. BRD9 is overexpressed in many malignancies, including CRC ( Figure 1 ) and Gastrointestinal Stromal Tumors (GISTs) [ 33 ]. We observed that siRNA-mediated loss of BRD9 expression in human colon cancer cells produced marked changes in phenotypic and molecular readouts ( Figure 2 ), consistent with the overarching goal of targeting oncogenic functions arising from BRD9 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…The imperfect association between loss of BRD9 and c-Myc expression implicated additional factors in downregulating the oncoprotein in colon cancer cells. Multiple BRD9-binding sites reside within MYC enhancer elements [ 33 , 37 ], with various multiprotein complexes differentially regulating apoptosis outcomes in CRC and other malignancies [ 33 , 38 , 39 , 40 ]. Similarly, the lack of a good association between BRD9 expression and the phenotypic markers ( Figure 4 ) can be attributed to additional effects of polyphenols on other molecular targets and signaling pathways that regulate antioxidant, anti-inflammatory, anti-proliferative, and cell cycle inhibitory actions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in abundance of protein in loading controls (αtubulin, actin, β-catenin) between samples exposed to genomic stress were observed; therefore, samples were normalized by loading equivalent protein (30 μg) in each lane (as determined through BCA assay). The following well characterized primary antibodies were used for studies included in this publication: Total p53 99 , phosphorylated-p53 98 , pChk2 100 , αtubulin 101 , β-catenin 102 , Total H2Ax 103 , and γ-H2AX 104 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that the AKT/mTOR signaling pathway is one of the key pathways activated by TUFT1 to promote tumor growth and metastasis. 18,20,22 Based on these results, we detected whether AKT activation is influenced by TUFT1 SUMOylation.…”
Section: Tuft1 Sumoylation Is Necessary For Akt/mtor Signaling Pathwa...mentioning
confidence: 99%
“…Oncological studies indicate that TUFT1 is highly expressed in various tumors, predicting worse clinical outcomes and poorer prognosis 18–21 . In GC, TUFT1 promotes tumor growth and metastasis by activating AKT and related downstream pathways 22 . Alternatively, TUFT1 directly modulates the activity of mTORC1 by regulating the intracellular lysosome localization and cellular trafficking of Rab GTPases 19 .…”
Section: Introductionmentioning
confidence: 99%